A large-capacity hydrogen-carbon battery and its preparation method
By coating the lithium lanthanum composite filler-graphene oxide composite on the separator of the hydrogen carbon battery and preparing the separator by coaxial electrospinning method, the problems of existing hydrogen carbon batteries in catalyst stability, battery life and electrode material preparation methods are solved, and high specific capacity and good electrochemical performance are achieved.
Patent Information
- Application Number
- CN202410603648.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-05-15
AI Technical Summary
The existing hydrogen carbon batteries have problems such as catalyst stability, battery life and electrode material preparation methods in terms of preparation and performance, resulting in insufficient capacity and performance.
The separator was prepared by coaxial electrospinning method, and nanosilicon dioxide microspheres were grown in situ in the mixed liquid of ethyl orthosilicate to improve the heat resistance of the separator. At the same time, the lithium lanthanum composite filler-graphene oxide composite slurry is coated on the separator, and the good ionic conductivity and compatibility with metal lithium are utilized, combined with the high conductivity and large specific surface area of graphene, the specific capacity of the battery is improved.
The high specific capacity and good electrochemical performance of hydrogen carbon batteries have been achieved, especially in terms of heat resistance and lithium ion diffusion speed.
Smart Images

Figure BDA0004841354630000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a large-capacity hydrogen-carbon battery and a preparation method thereof. Background Art
[0002] With the continuous growth of energy demand and the urgent need for clean energy, hydrogen-carbon batteries have attracted widespread attention as an efficient and clean energy storage and conversion technology. Hydrogen-carbon batteries use hydrogen and carbon sources as fuels to generate electricity through electrochemical reactions. Compared with traditional batteries, hydrogen-carbon batteries have the advantages of high energy density, low emissions, and renewability, so they are considered to be a potential green energy technology.
[0003] However, existing hydrogen-carbon batteries still face some challenges in preparation and performance. These include the stability of the catalyst, battery life, preparation methods of electrode materials, etc. Therefore, a new type of large-capacity hydrogen-carbon battery and a corresponding preparation method are urgently needed to overcome these challenges and improve the performance of hydrogen-carbon batteries.
[0004] In order to solve the above problems and improve the capacity of the hydrogen-carbon battery, the present invention provides a large-capacity hydrogen-carbon battery and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a large-capacity hydrogen-carbon battery and a preparation method thereof to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a large-capacity hydrogen-carbon battery comprises the following steps:
[0008] Step 1: using a core layer spinning solution and a shell layer spinning solution, a diaphragm is prepared by a coaxial electrospinning method, and then dried to obtain a film;
[0009] Step 2: Take ethyl orthosilicate and anhydrous ethanol, stir evenly, add ammonia water, stir for 30-40 minutes to obtain a mixed solution; take a film, add deionized water to make the film fully wetted, add the mixed solution, soak for 70-74 hours, wash and dry to obtain a diaphragm;
[0010] Step 3: Take a lithium lanthanum composite filler-graphene oxide composite and N-methylpyrrolidone, ultrasonically disperse them, add polyvinylidene fluoride, stir for 12-14 hours, and obtain a slurry; evenly coat the slurry on the diaphragm, dry it, and obtain a modified diaphragm;
[0011] Step 3: Take the positive electrode, modified diaphragm, and negative electrode, assemble them, and inject electrolyte to obtain a large-capacity hydrogen-carbon battery.
[0012] More optimally, the preparation method of the lithium lanthanum composite filler-graphene oxide composite is: take modified lithium lanthanum composite filler and deionized water, ultrasonically disperse for 40-50 minutes, add modified graphene oxide, dropwise add ammonia solution, stir for 30-50 minutes, filter, wash, and dry to obtain a lithium lanthanum composite filler-graphene oxide composite.
[0013] More optimally, the preparation method of the modified lithium lanthanum composite filler is: take the lithium lanthanum composite filler and deionized water, ultrasonically disperse for 50-60 minutes, add dopamine, add Tris-HCl buffer, adjust the pH value to 8.5, stir for 22-26 hours, filter, wash, and dry to obtain the modified lithium lanthanum composite filler.
[0014] More optimally, the preparation method of the lithium lanthanum composite filler is: take lithium hydroxide monohydrate, lanthanum hydroxide, tantalum oxide, and zirconium oxide powders, add zirconium oxide grinding balls, add anhydrous ethanol to cover the raw materials and the grinding balls, grind for 10-14 hours, dry and grind, calcine at 900-920°C for 10-14 hours, and grind again to obtain a lithium lanthanum composite filler.
[0015] More optimally, the particle size of the lithium lanthanum composite filler is 50-80 nm.
[0016] More optimally, the preparation method of the modified graphene oxide is: take 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, add it to a mixed solution of ethanol and water, and stir evenly; add graphene oxide, heat to 60-65°C, stir for 8-10h, and obtain modified graphene oxide.
[0017] More optimally, the mass ratio of the modified lithium lanthanum composite filler to the modified graphene oxide is (3-3.5):2.
[0018] More optimally, in step 1, the method for preparing the core layer spinning solution is: taking polyetherimide, adding N-methylpyrrolidone and tetrahydrofuran mixed solution, heating to 80-85° C., stirring for 5-7 hours, and standing to obtain the core layer spinning solution;
[0019] The method for preparing the shell spinning solution is as follows: taking polyvinylidene fluoride, adding N-methylpyrrolidone and tetrahydrofuran mixed solution, heating to 58-62° C., stirring for 5-7 hours, and standing to obtain the shell spinning solution.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] (1) The present invention uses a polyetherimide solution as a core layer spinning solution and a polyvinylidene fluoride solution as a shell layer spinning solution, and prepares a diaphragm by coaxial electrospinning. The diaphragm is then immersed in a tetraethyl orthosilicate mixed solution, and nano-silica microspheres are in situ grown on the surface of the diaphragm. The battery prepared using the diaphragm has good heat resistance.
[0022] (2) The present invention coats a slurry containing a lithium lanthanum composite filler-graphene oxide composite on the diaphragm. The lithium lanthanum composite filler has good ionic conductivity and good compatibility with metallic lithium. The lithium lanthanum composite filler is applied to the diaphragm, and the prepared battery exhibits a higher specific capacity. Graphene has a higher conductivity and a larger specific surface area. The lithium lanthanum composite filler is compounded with graphene. On the one hand, the two-dimensional structure of graphene helps to increase the lithium ion embedding rate, thereby enhancing the diffusion rate of lithium ions and improving the electrochemical performance of the diaphragm. On the other hand, the compounding of graphene can improve the dispersibility of the lithium lanthanum composite filler in the slurry.
[0023] The present invention uses 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane to modify graphene oxide, and grafts epoxy groups on the graphene oxide. The epoxy groups have good lipophilicity and good compatibility with N-methylpyrrolidone, and can improve the dispersibility of the lithium lanthanum composite filler-graphene oxide composite, thereby improving the capacity of the hydrogen-carbon battery. Then, the present invention adds dopamine to compound the modified graphene oxide and the lithium lanthanum composite filler. At this time, the amino group on the lithium lanthanum composite filler-graphene oxide composite can react with the silicon hydroxyl group on the diaphragm, so that the two are closely combined together, thereby improving the capacity of the hydrogen-carbon battery. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] There is no special restriction on the manufacturers of all raw materials involved in the present invention, and exemplary examples include: lithium hydroxide monohydrate, lanthanum hydroxide, tantalum oxide, and zirconium oxide powders can all be purchased from Aladdin with a purity of 99.9%; polyvinylidene fluoride: can be purchased from Shanghai Yuanye, model: S63756; 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane: can be purchased from Wuhan Kanos Technology Co., Ltd.; graphene oxide: can be purchased from Merck, model: 796034; stainless steel flange-connected ball valve: can be purchased from Swagelok.
[0026] Embodiment 1: A method for preparing a large-capacity hydrogen-carbon battery, comprising the following steps:
[0027] Step 1: Preparation of modified lithium lanthanum composite filler:
[0028] Take 25g of lithium hydroxide monohydrate, 17g of lanthanum hydroxide, 11g of tantalum oxide, and 6g of zirconium oxide powder, add 200g of zirconium oxide grinding balls, add anhydrous ethanol to cover the raw materials and the grinding balls, grind for 11 hours, dry and grind, calcine at 910°C for 12 hours, and grind again to obtain a lithium lanthanum composite filler;
[0029] Take 5g of lithium lanthanum composite filler and 100mL of deionized water, ultrasonically disperse for 55min, add 10g of dopamine, add Tris-HCl buffer, adjust the pH value to 8.5, stir for 24h, filter, wash, and dry to obtain a modified lithium lanthanum composite filler;
[0030] Step 2: Preparation of modified graphene oxide:
[0031] Take 3 mL of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, add it to a mixed solution of ethanol and water with a volume ratio of 90:10, and stir evenly; add 1 g of graphene oxide, heat to 63°C, and stir for 9 hours to obtain modified graphene oxide;
[0032] Step 3: Preparation of lithium lanthanum composite filler-graphene oxide composite:
[0033] Take 3 g of modified lithium lanthanum composite filler and 100 mL of deionized water, ultrasonically disperse for 45 min, add 2 g of modified graphene oxide, dropwise add ammonia solution, stir for 40 min, filter, wash, and dry to obtain a lithium lanthanum composite filler-graphene oxide composite;
[0034] The preparation method of the ammonia solution is as follows: 7 g of ammonia solution and 120 mL of deionized water are mixed and stirred to obtain an ammonia solution;
[0035] Step 4: Preparation of modified diaphragm:
[0036] Take 25g of polyetherimide, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 83°C, stir for 6h, and stand to obtain core layer spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0037] Take 20g of polyvinylidene fluoride, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 60°C, stir for 6h, and stand to obtain shell spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0038] Using a core layer spinning solution and a shell layer spinning solution, the core layer propulsion rate is 0.15mL / h, and the shell layer propulsion rate is 0.3mL / h, and a diaphragm is prepared by a coaxial electrospinning method, and dried to obtain a film;
[0039] Take 10g of tetraethyl orthosilicate and 50mL of anhydrous ethanol, stir evenly, add 3mL of ammonia water, stir for 35min to obtain a mixed solution; take a 10cm×15cm film, add deionized water to fully wet the film, add the mixed solution, soak for 72h, wash and dry to obtain a diaphragm;
[0040] Step 5: Preparation of modified diaphragm:
[0041] Take 6 g of lithium lanthanum composite filler-graphene oxide composite and 100 mL of N-methylpyrrolidone, disperse by ultrasonication, add 10 g of polyvinylidene fluoride, stir for 13 h to obtain slurry; evenly coat the slurry on the diaphragm, dry, and obtain a modified diaphragm;
[0042] Step 6: Preparation of large-capacity hydrogen-carbon battery:
[0043] The battery shell is a stainless steel flange-connected ball valve. The inside of the battery is a positive electrode, a negative electrode and a diaphragm material assembled in a buckle form. The diaphragm is filled with 9M H3PO4 electrolyte. The positive electrode is made of commercially available activated carbon coated on titanium foil, and the negative electrode is made of commercially available platinum carbon coated on the gas diffusion layer substrate. The electrical adsorption capacity of the electrode is 0.5mAh / cm 2 .
[0044] Embodiment 2: A method for preparing a large-capacity hydrogen-carbon battery, comprising the following steps:
[0045] Step 1: Preparation of modified lithium lanthanum composite filler:
[0046] Take 25g of lithium hydroxide monohydrate, 17g of lanthanum hydroxide, 11g of tantalum oxide, and 6g of zirconium oxide powder, add 200g of zirconium oxide grinding balls, add anhydrous ethanol to cover the raw materials and the grinding balls, grind for 10 hours, dry and grind, calcine at 900°C for 10 hours, and grind again to obtain a lithium lanthanum composite filler;
[0047] Take 5g of lithium lanthanum composite filler and 100mL of deionized water, ultrasonically disperse for 50min, add 10g of dopamine, add Tris-HCl buffer, adjust the pH value to 8.5, stir for 22h, filter, wash, and dry to obtain a modified lithium lanthanum composite filler;
[0048] Step 2: Preparation of modified graphene oxide:
[0049] Take 3 mL of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, add it to a mixed solution of ethanol and water with a volume ratio of 90:10, and stir evenly; add 1 g of graphene oxide, heat to 60°C, and stir for 8 hours to obtain modified graphene oxide;
[0050] Step 3: Preparation of lithium lanthanum composite filler-graphene oxide composite:
[0051] Take 3 g of modified lithium lanthanum composite filler and 100 mL of deionized water, ultrasonically disperse for 40 min, add 2 g of modified graphene oxide, dropwise add ammonia solution, stir for 30 min, filter, wash, and dry to obtain a lithium lanthanum composite filler-graphene oxide composite;
[0052] The preparation method of the ammonia solution is as follows: 7 g of ammonia solution and 120 mL of deionized water are mixed and stirred to obtain an ammonia solution;
[0053] Step 4: Preparation of modified diaphragm:
[0054] Take 25g of polyetherimide, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 80°C, stir for 5h, and let stand to obtain core layer spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0055] Take 20g of polyvinylidene fluoride, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 58°C, stir for 5h, and let stand to obtain shell spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0056] Using a core layer spinning solution and a shell layer spinning solution, the core layer propulsion rate is 0.15mL / h, and the shell layer propulsion rate is 0.3mL / h, and a diaphragm is prepared by a coaxial electrospinning method, and dried to obtain a film;
[0057] Take 10g of tetraethyl orthosilicate and 50mL of anhydrous ethanol, stir evenly, add 3mL of ammonia water, stir for 30min to obtain a mixed solution; take a 10cm×15cm film, add deionized water to make the film fully wetted, add the mixed solution, soak for 70h, wash and dry to obtain a diaphragm;
[0058] Step 5: Preparation of modified diaphragm:
[0059] Take 6 g of lithium lanthanum composite filler-graphene oxide composite and 100 mL of N-methylpyrrolidone, disperse by ultrasonication, add 10 g of polyvinylidene fluoride, stir for 12 h to obtain slurry; evenly coat the slurry on the diaphragm, dry, and obtain a modified diaphragm;
[0060] Step 6: Preparation of large-capacity hydrogen-carbon battery:
[0061] The battery shell is a stainless steel flange-connected ball valve. The inside of the battery is a positive electrode, a negative electrode and a diaphragm material assembled in a buckle form. The diaphragm is filled with 9M H3PO4 electrolyte. The positive electrode is made of commercially available activated carbon coated on titanium foil, and the negative electrode is made of commercially available platinum carbon coated on the gas diffusion layer substrate. The electrical adsorption capacity of the electrode is 0.5mAh / cm 2 .
[0062] Embodiment 3: A method for preparing a large-capacity hydrogen-carbon battery, comprising the following steps:
[0063] Step 1: Preparation of modified lithium lanthanum composite filler:
[0064] Take 25g of lithium hydroxide monohydrate, 17g of lanthanum hydroxide, 11g of tantalum oxide, and 6g of zirconium oxide powder, add 200g of zirconium oxide grinding balls, add anhydrous ethanol to cover the raw materials and the grinding balls, grind for 14 hours, dry and grind, calcine at 920°C for 14 hours, and grind again until the powder particle size is 80nm to obtain a lithium lanthanum composite filler;
[0065] Take 5g of lithium lanthanum composite filler and 100mL of deionized water, ultrasonically disperse for 60min, add 10g of dopamine, add Tris-HCl buffer, adjust the pH value to 8.5, stir for 26h, filter, wash, and dry to obtain a modified lithium lanthanum composite filler;
[0066] Step 2: Preparation of modified graphene oxide:
[0067] Take 3 mL of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, add it to a mixed solution of ethanol and water with a volume ratio of 90:10, and stir evenly; add 1 g of graphene oxide, heat to 65°C, and stir for 10 hours to obtain modified graphene oxide;
[0068] Step 3: Preparation of lithium lanthanum composite filler-graphene oxide composite:
[0069] Take 3 g of modified lithium lanthanum composite filler and 100 mL of deionized water, ultrasonically disperse for 50 min, add 2 g of modified graphene oxide, dropwise add ammonia solution, stir for 50 min, filter, wash, and dry to obtain a lithium lanthanum composite filler-graphene oxide composite;
[0070] The preparation method of the ammonia solution is as follows: 7 g of ammonia solution and 120 mL of deionized water are mixed and stirred to obtain an ammonia solution;
[0071] Step 4: Preparation of modified diaphragm:
[0072] Take 25g of polyetherimide, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 85°C, stir for 7h, and let stand to obtain core layer spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0073] Take 20g of polyvinylidene fluoride, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 62°C, stir for 7h, and stand to obtain shell spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0074] Using a core layer spinning solution and a shell layer spinning solution, the core layer propulsion rate is 0.15mL / h, and the shell layer propulsion rate is 0.3mL / h, and a diaphragm is prepared by a coaxial electrospinning method, and dried to obtain a film;
[0075] Take 10g of tetraethyl orthosilicate and 50mL of anhydrous ethanol, stir evenly, add 3mL of ammonia water, stir for 40min to obtain a mixed solution; take a 10cm×15cm film, add deionized water to fully wet the film, add the mixed solution, soak for 74h, wash and dry to obtain a diaphragm;
[0076] Step 5: Preparation of modified diaphragm:
[0077] Take 6 g of lithium lanthanum composite filler-graphene oxide composite and 100 mL of N-methylpyrrolidone, disperse by ultrasonication, add 10 g of polyvinylidene fluoride, stir for 14 h to obtain slurry; evenly coat the slurry on the diaphragm, dry, and obtain a modified diaphragm;
[0078] Step 6: Preparation of large-capacity hydrogen-carbon battery:
[0079] The battery shell is a stainless steel flange-connected ball valve. The inside of the battery is a positive electrode, a negative electrode and a diaphragm material assembled in a buckle form. The diaphragm is filled with 9M H3PO4 electrolyte. The positive electrode is made of commercially available activated carbon coated on titanium foil, and the negative electrode is made of commercially available platinum carbon coated on the gas diffusion layer substrate. The electrical adsorption capacity of the electrode is 0.5mAh / cm 2 .
[0080] Comparative Example 1: Graphene oxide is not modified, and the rest is the same as Example 1:
[0081] Step 1: Preparation of modified lithium lanthanum composite filler:
[0082] Take 25g of lithium hydroxide monohydrate, 17g of lanthanum hydroxide, 11g of tantalum oxide, and 6g of zirconium oxide powder, add 200g of zirconium oxide grinding balls, add anhydrous ethanol to cover the raw materials and the grinding balls, grind for 11 hours, dry and grind, calcine at 910°C for 12 hours, and grind again to obtain a lithium lanthanum composite filler;
[0083] Take 5g of lithium lanthanum composite filler and 100mL of deionized water, ultrasonically disperse for 55min, add 10g of dopamine, add Tris-HCl buffer, adjust the pH value to 8.5, stir for 24h, filter, wash, and dry to obtain a modified lithium lanthanum composite filler;
[0084] Step 2: Preparation of modified graphene oxide:
[0085] Take 3 mL of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, add it to a mixed solution of ethanol and water with a volume ratio of 90:10, and stir evenly; add 1 g of graphene oxide, heat to 63°C, and stir for 9 hours to obtain modified graphene oxide;
[0086] Step 3: Preparation of lithium lanthanum composite filler-graphene oxide composite:
[0087] Take 3 g of modified lithium lanthanum composite filler and 100 mL of deionized water, ultrasonically disperse for 45 min, add 2 g of modified graphene oxide, dropwise add ammonia solution, stir for 40 min, filter, wash, and dry to obtain a lithium lanthanum composite filler-graphene oxide composite;
[0088] The preparation method of the ammonia solution is as follows: 7 g of ammonia solution and 120 mL of deionized water are mixed and stirred to obtain an ammonia solution;
[0089] Step 4: Preparation of modified diaphragm:
[0090] Take 25g of polyetherimide, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 83°C, stir for 6h, and stand to obtain core layer spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0091] Take 20g of polyvinylidene fluoride, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 60°C, stir for 6h, and stand to obtain shell spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0092] Using a core layer spinning solution and a shell layer spinning solution, the core layer propulsion rate is 0.15mL / h, and the shell layer propulsion rate is 0.3mL / h, and a diaphragm is prepared by a coaxial electrospinning method, and dried to obtain a film;
[0093] Take 10g of tetraethyl orthosilicate and 50mL of anhydrous ethanol, stir evenly, add 3mL of ammonia water, stir for 35min to obtain a mixed solution; take a 10cm×15cm film, add deionized water to fully wet the film, add the mixed solution, soak for 72h, wash and dry to obtain a diaphragm;
[0094] Step 5: Preparation of modified diaphragm:
[0095] Take 6 g of lithium lanthanum composite filler-graphene oxide composite and 100 mL of N-methylpyrrolidone, disperse by ultrasonication, add 10 g of polyvinylidene fluoride, stir for 13 h to obtain slurry; evenly coat the slurry on the diaphragm, dry, and obtain a modified diaphragm;
[0096] Step 6: Preparation of large-capacity hydrogen-carbon battery:
[0097] The battery shell is a stainless steel flange-connected ball valve. The inside of the battery is a positive electrode, a negative electrode and a diaphragm material assembled in a buckle form. The diaphragm is filled with 9M H3PO4 electrolyte. The positive electrode is made of commercially available activated carbon coated on titanium foil, and the negative electrode is made of commercially available platinum carbon coated on the gas diffusion layer substrate. The electrical adsorption capacity of the electrode is 0.5mAh / cm 2 .
[0098] Comparative Example 2: The lithium-lanthanum composite filler is not modified, and the rest is the same as Example 1:
[0099] Step 1: Preparation of modified lithium lanthanum composite filler:
[0100] Take 25g of lithium hydroxide monohydrate, 17g of lanthanum hydroxide, 11g of tantalum oxide, and 6g of zirconium oxide powder, add 200g of zirconium oxide grinding balls, add anhydrous ethanol to cover the raw materials and the grinding balls, grind for 11 hours, dry and grind, calcine at 910°C for 12 hours, and grind again to obtain a lithium lanthanum composite filler;
[0101] Take 5g of lithium lanthanum composite filler and 100mL of deionized water, ultrasonically disperse for 55min, add 10g of dopamine, add Tris-HCl buffer, adjust the pH value to 8.5, stir for 24h, filter, wash, and dry to obtain a modified lithium lanthanum composite filler;
[0102] Step 2: Preparation of modified graphene oxide:
[0103] Take 3 mL of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, add it to a mixed solution of ethanol and water with a volume ratio of 90:10, and stir evenly; add 1 g of graphene oxide, heat to 63°C, and stir for 9 hours to obtain modified graphene oxide;
[0104] Step 3: Preparation of lithium lanthanum composite filler-graphene oxide composite:
[0105] Take 3 g of modified lithium lanthanum composite filler and 100 mL of deionized water, ultrasonically disperse for 45 min, add 2 g of modified graphene oxide, dropwise add ammonia solution, stir for 40 min, filter, wash, and dry to obtain a lithium lanthanum composite filler-graphene oxide composite;
[0106] The preparation method of the ammonia solution is as follows: 7 g of ammonia solution and 120 mL of deionized water are mixed and stirred to obtain an ammonia solution;
[0107] Step 4: Preparation of modified diaphragm:
[0108] Take 25g of polyetherimide, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 83°C, stir for 6h, and stand to obtain core layer spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0109] Take 20g of polyvinylidene fluoride, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 60°C, stir for 6h, and stand to obtain shell spinning solution; the mass ratio of N-methylpyrrolidone to tetrahydrofuran is 9:1;
[0110] Using a core layer spinning solution and a shell layer spinning solution, the core layer propulsion rate is 0.15mL / h, and the shell layer propulsion rate is 0.3mL / h, and a diaphragm is prepared by a coaxial electrospinning method, and dried to obtain a film;
[0111] Take 10g of tetraethyl orthosilicate and 50mL of anhydrous ethanol, stir evenly, add 3mL of ammonia water, stir for 35min to obtain a mixed solution; take a 10cm×15cm film, add deionized water to fully wet the film, add the mixed solution, soak for 72h, wash and dry to obtain a diaphragm;
[0112] Step 5: Preparation of modified diaphragm:
[0113] Take 6 g of lithium lanthanum composite filler-graphene oxide composite and 100 mL of N-methylpyrrolidone, disperse by ultrasonication, add 10 g of polyvinylidene fluoride, stir for 13 h to obtain slurry; evenly coat the slurry on the diaphragm, dry, and obtain a modified diaphragm;
[0114] Step 6: Preparation of large-capacity hydrogen-carbon battery:
[0115] The battery shell is a stainless steel flange-connected ball valve. The inside of the battery is a positive electrode, a negative electrode and a diaphragm material assembled in a buckle form. The diaphragm is filled with 9M H3PO4 electrolyte. The positive electrode is made of commercially available activated carbon coated on titanium foil, and the negative electrode is made of commercially available platinum carbon coated on the gas diffusion layer substrate. The electrical adsorption capacity of the electrode is 0.5mAh / cm 2 .
[0116] experiment:
[0117] The performance test of the battery prepared in Example 1-3 and Comparative Example 1-2 was carried out, and the charge and discharge voltage range was 1.7-2.8V, and the current density was 0.2C (1C = 1675mAh·g -1), under 0.2C conditions, the initial capacity and the capacity after 100 cycles were tested, and the obtained data are shown in the following table:
[0118]
[0119] Conclusion: In comparative example 1, graphene oxide is not modified, the dispersibility of the lithium lanthanum composite filler-graphene oxide composite is deteriorated, and the capacity of the battery is reduced. In comparative example 2, the lithium lanthanum composite filler is not modified, the bonding force between the lithium lanthanum composite filler-graphene oxide composite and the diaphragm is deteriorated, and the capacity of the hydrogen-carbon battery is reduced. In Example 1-3, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane is used to modify graphene oxide, and epoxy groups are grafted on graphene oxide. The epoxy groups have good lipophilicity and good compatibility with N-methylpyrrolidone, which can improve the dispersibility of the lithium lanthanum composite filler-graphene oxide composite, thereby improving the capacity of the hydrogen-carbon battery. The amino groups on the lithium lanthanum composite filler-graphene oxide composite can react with the silicon hydroxyl groups on the diaphragm, so that the two are tightly combined together, thereby improving the capacity of the hydrogen-carbon battery.
[0120] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a large-capacity hydrogen-carbon battery, characterized in that: The following steps are involved: Step 1: using a core layer spinning solution and a shell layer spinning solution, a diaphragm is prepared by a coaxial electrospinning method, and then dried to obtain a film; Step 2: Take ethyl orthosilicate and anhydrous ethanol, stir evenly, add ammonia water, stir for 30-40 minutes to obtain a mixed solution; take a film, add deionized water to make the film fully wetted, add the mixed solution, soak for 70-74 hours, wash and dry to obtain a diaphragm; Step 3: Take a lithium lanthanum composite filler-graphene oxide composite and N-methylpyrrolidone, ultrasonically disperse them, add polyvinylidene fluoride, stir for 12-14 hours, and obtain a slurry; evenly coat the slurry on the diaphragm, dry it, and obtain a modified diaphragm; Step 3: Take the positive electrode, modified diaphragm, and negative electrode, assemble them, inject electrolyte, and obtain a large-capacity hydrogen-carbon battery; The preparation method of the lithium lanthanum composite filler-graphene oxide composite is as follows: taking a modified lithium lanthanum composite filler and deionized water, ultrasonically dispersing for 40-50 minutes, adding modified graphene oxide, dripping an ammonia solution, stirring for 30-50 minutes, filtering, washing, and drying to obtain a lithium lanthanum composite filler-graphene oxide composite; The preparation method of the modified lithium lanthanum composite filler is as follows: taking the lithium lanthanum composite filler and deionized water, ultrasonically dispersing for 50-60 minutes, adding dopamine, adding Tris-HCl buffer, adjusting the pH value to 8.5, stirring for 22-26 hours, filtering, washing, and drying to obtain the modified lithium lanthanum composite filler; The preparation method of the lithium lanthanum composite filler is as follows: lithium hydroxide monohydrate, lanthanum hydroxide, tantalum oxide, and zirconium oxide powder are taken, zirconium oxide grinding balls are added, anhydrous ethanol is added to cover the raw materials and the grinding balls, and the mixture is ground for 10-14 hours, dried, ground, calcined at 900-920° C. for 10-14 hours, and ground again to obtain the lithium lanthanum composite filler; In step 1, the preparation method of the core layer spinning solution is as follows: take polyetherimide, add N-methylpyrrolidone and tetrahydrofuran mixed solution, heat to 80-85° C., stir for 5-7 hours, and stand to obtain the core layer spinning solution; The method for preparing the shell spinning solution is as follows: taking polyvinylidene fluoride, adding N-methylpyrrolidone and tetrahydrofuran mixed solution, heating to 58-62° C., stirring for 5-7 hours, and standing to obtain the shell spinning solution.
2. The method for preparing a large-capacity hydrogen-carbon battery according to claim 1, characterized in that: The particle size of the lithium-lanthanum composite filler is 50-80 nm.
3. The method for preparing a large-capacity hydrogen-carbon battery according to claim 1, characterized in that: The preparation method of the modified graphene oxide is as follows: taking 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, adding it to a mixed solution of ethanol and water, and stirring it evenly; adding graphene oxide, heating it to 60-65° C., and stirring it for 8-10 hours to obtain the modified graphene oxide.
4. The method for preparing a large-capacity hydrogen-carbon battery according to claim 1, characterized in that: The mass ratio of the modified lithium lanthanum composite filler to the modified graphene oxide is (3-3.5):
2.
5. A large-capacity hydrogen-carbon battery prepared according to the method for preparing a large-capacity hydrogen-carbon battery according to any one of claims 1 to 4.
Citation Information
Patent Citations
Nanofiber with core-shell structure, diaphragm, preparation method of nanofiber and preparation method of diaphragm, and battery
CN117328164A
Conductive aromatic polyimide porous film and method for producing same
US20180051172A1